2022
DOI: 10.22342/jme.v13i3.pp499-514
|View full text |Cite
|
Sign up to set email alerts
|

Developing RME-based lesson study for learning community in the learning environment of high school mathematics teachers

Abstract: Teachers' academic and professional competencies significantly improve the quality of their learning. An ongoing process is needed to support and develop their quality. This study developed a learning environment through the Realistic Mathematics Education (RME)-based Lesson Study for Learning Community (LSLC) for high school mathematics teachers. The model is valid and practical and potentially affects the learning quality of high school mathematics teachers. The research employed a design research method of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…Student teachers felt great benefits from the learning environment and gained new knowledge. The findings of Fauziah et al (2020) and Rusiyanti et al (2022) revealed that the learning environment can be a means of developing the professional and pedagogical competencies of student teachers. The results of this study are linear with the statement that the learning environment is an important factor supporting the success of the teaching and learning process (Colbert, 2014;Durmus, 2016).…”
Section: Table 5 Comments and Suggestions From The Reviewersmentioning
confidence: 98%
“…Student teachers felt great benefits from the learning environment and gained new knowledge. The findings of Fauziah et al (2020) and Rusiyanti et al (2022) revealed that the learning environment can be a means of developing the professional and pedagogical competencies of student teachers. The results of this study are linear with the statement that the learning environment is an important factor supporting the success of the teaching and learning process (Colbert, 2014;Durmus, 2016).…”
Section: Table 5 Comments and Suggestions From The Reviewersmentioning
confidence: 98%
“…Lesson study is educational model that develops careers through collaborative and sustainable learning studies based on the principle of collective and mutual learning to build a learning community (Rusiyanti et al, 2022;Hidajat et al, 2018;Zhang et al, 2019). ISSN 2089-8703 (Print) Volume 12, No.…”
Section: Introductionmentioning
confidence: 99%
“…In-service teacher training programs improve teacher competence, talents, and attitudes (Cheung, 2013). Teacher training has been carried out in various places to improve teacher professionalism (Jablonski et al, 2018(Jablonski et al, , 2021Milicic et al, 2020;Rusiyanti et al, 2022;Sala-Sebastià et al, 2022;Suryanti et al, 2022;Taranto et al, 2021). According to Hattie (2008), the four most effective ways of teacher knowledge and behavior education are observation of real-world classroom processes, microteaching, video/audio feedback, and practice.…”
mentioning
confidence: 99%